Nationwide-free preconception care strategy: Experience from China - Xu, Jinghui; Li, Xiaotian; Zhou, Qiongjie (Frontiers in Public Health, 2022)
Preconception care has emerged as a developing field in maternal and child healthcare worldwide. This care type provides couples of reproductive age with the opportunity for early detection and management of biomedical, behavioral and social health problems. In 2010, the Chinese government launched a nationwide preconception care program as a welfare project. During the past decade, this project has received international attention, and experiences from the project have been published in the literature. In this review, we summarize the history, implementation, and evaluation of preconception care services in China, and its related maternal and children’s health service initiatives, to thereby provide knowledge for policymakers and clinicians in other countries.